Study on the anti-vibrio activity of marine fungi Aspergillus sydowii and Rhizopus sp. using OSMAC Approach - Galank Fad'qul Janarkho; Agus Trianto; Sri Sedjati; Rindiani Puja Listari (Universitas Diponegoro, 2023)
Shrimp is one of the major aquaculture products in Indonesia. However, shrimp culture faces the peril of Vibriosis, a disease caused by the bacteria genus of Vibrio. Marine sponge-associate microbes are recognized for their potential as sources of antibacterial agent. The fungus Aspergillus sydowii isolate that used in this research originally isolated from marine sponge collected in Lampung Bay. The fungus was grown in various media e. g. Malt extract agar (MEA), MEA-Tempeh broth (MEA-T), and tofu dregs (TD) under various pH (5.5, 7.5, and 9.5). The fungus also be culture as mono-culture and co-culture with Rhizopus sp. The anti-vibrio assay was conducted using disk diffusion method. Based on anti-vibrio assay, the fungus A. sydowii and Rhizopus sp. didn’t show any correlation with the anti-vibrio compound produced. The fungus Rhizopus sp. cultivated in tofu dregs media (TD) at pH 5.5 exhibited the highest potential for inhibiting against V. alginolyticus (5.85±0.24 mm), V. harveyi (5.20±0.20 mm), and V. vulnificus (4.33±0.15 mm), while the co-culture (A. sydowii and Rhizopus sp.) in TD media and pH 7.5 against V. parahaemolyticus (5.55±0.86 mm). The fungus cultured in pH 7.5 can promotes the potential inhibition zone than a pH 9.5.